Net nutrition on the late 19th and early 20th century American Great Plains: a robust biological response to the challenges to the Turner Hypothesis. Issue 5 (26th February 2019) - Carson, Scott Alan
Abstract: In 1893, Frederick Jackson Turner proposed that America's Western frontier was an economic 'safety-valve' – a place where settlers could migrate when conditions in eastern states and Europe crystallized against their upward economic mobility. However, recent studies suggest the Western frontier's material conditions may not have been as advantageous as Jackson proposed because settlers lacked the knowledge and human capital to succeed on the Plains and Far Western frontier. Using stature, BMI and weight from five late 19 th and early 20 th century prisons, this study uses 61, 276 observations for men between ages 15 and 79 to illustrate that current and cumulative net nutrition on the Great Plains did not deteriorate during the late 19 th and early 20 th centuries, indicating that recent challenges to the Turner Hypothesis are not well supported by net nutrition studies.